Execution / 5 - Smith, Alexander Gordon, 1979- (Escape from Furnace, 2012)
Alex Sawyer has escaped his underground nightmare to discover that the whole world has become a horrible prison run by his nemesis, Alfred Furnace, and only Alex can stop him, even if that makes him the executioner.